2022
DOI: 10.3390/biology11050755
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Epidemiology of Tuberculosis in Thailand from 2011 to 2020

Abstract: Tuberculosis is a leading cause of infectious disease globally, especially in developing countries. Better knowledge of spatial and temporal patterns of tuberculosis burden is important for effective control programs as well as informing resource and budget allocation. Studies have demonstrated that TB exhibits highly complex dynamics in both spatial and temporal dimensions at different levels. In Thailand, TB research has been primarily focused on surveys and clinical aspects of the disease burden with little… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
(50 reference statements)
0
0
0
Order By: Relevance
“…indicate that the TB cases in Aceh Province were geographically dispersed at the districts level. Our findings contradicted with previous studies in Thailand [23] and China [24] where the TB incidence were geographically clustered due to the TB incidence in both a particular spatial unit and its neighbouring unit either surpassing or falling below the mean. While in our study, the TB incidence in a particular spatial unit and its neighbouring unit diverged on the opposite side of the mean.…”
Section: Global Autocorrelationcontrasting
confidence: 99%
See 2 more Smart Citations
“…indicate that the TB cases in Aceh Province were geographically dispersed at the districts level. Our findings contradicted with previous studies in Thailand [23] and China [24] where the TB incidence were geographically clustered due to the TB incidence in both a particular spatial unit and its neighbouring unit either surpassing or falling below the mean. While in our study, the TB incidence in a particular spatial unit and its neighbouring unit diverged on the opposite side of the mean.…”
Section: Global Autocorrelationcontrasting
confidence: 99%
“…Although Langsa is not the capital city of Aceh Province, it is considered to be one of the major cities in Aceh Province with better healthcare facilities. A study in Thailand found a spatial pattern of TB incidence in Thai borderland and seemingly related to the migrants' behaviour from Laos to find a better healthcare facility in Thai borderland [23]. However, further investigation on the association between spatial pattern of TB case distribution and mobility behaviour of the population is highly suggested to understand the spatial pattern of TB incidence in borderland of Aceh Province.…”
Section: Local Autocorrelation and Hot-spot Analysismentioning
confidence: 99%
See 1 more Smart Citation